2009
DOI: 10.1103/physrevlett.102.195505
|View full text |Cite
|
Sign up to set email alerts
|

Fabrication of a Freestanding Boron Nitride Single Layer and Its Defect Assignments

Abstract: A freestanding single layer of hexagonal boron nitride (h-BN) has been successfully fabricated by controlled energetic electron irradiation through a layer-by-layer sputtering process. We have successfully resolved atomic defects in h-BN with triangle shapes by means of an aberration corrected high-resolution transmission electron microscopy with exit-wave reconstruction. Boron monovacancies are found to be preferably formed and the dominating zigzag-type edges are proved to be nitrogen terminated.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

52
804
4
9

Year Published

2010
2010
2023
2023

Publication Types

Select...
6
4

Relationship

0
10

Authors

Journals

citations
Cited by 1,076 publications
(869 citation statements)
references
References 22 publications
52
804
4
9
Order By: Relevance
“…The most likely candidates are a nitrogen vacancy (V N ), a boron vacancy (V B ) or an anti-site complex in which the nitrogen occupies the boron site and there is a missing atom at the nitrogen cite (N B V N ) 35,36 . We exclude the possibility of a di-vacancy as those have been shown to be highly unstable 37 . The V B has been theoretically predicted to have a UV absorption and emission band 36 that is inconsistent with our experimental data.…”
mentioning
confidence: 99%
“…The most likely candidates are a nitrogen vacancy (V N ), a boron vacancy (V B ) or an anti-site complex in which the nitrogen occupies the boron site and there is a missing atom at the nitrogen cite (N B V N ) 35,36 . We exclude the possibility of a di-vacancy as those have been shown to be highly unstable 37 . The V B has been theoretically predicted to have a UV absorption and emission band 36 that is inconsistent with our experimental data.…”
mentioning
confidence: 99%
“…The intriguing structural, electronic, and optical properties of many two-dimensional (2D) materials similar to graphene such as the transition-metal dichalcogenides [1][2][3], group IV elements [4,5], and group III-V based 2D materials [6][7][8] have motivated further research for new discoveries. Owing to its attractive intrinsic properties such as high carrier mobility, direct band gap, and superior optical properties, phosphorene has been widely in focus [9][10][11][12].…”
Section: Introductionmentioning
confidence: 99%
“…Early experimental studies aiming to synthesize and characterize novel monolayer materials have revealed that graphene-like sheets of BN are also stable. [29][30][31] Though BN has the same planar structure as graphene due to the ionic character of B-N bonds, BN crystal is a wide band gap insulator with an energy gap of 4.6 eV. [32][33][34][35] The perfect lattice matching between graphene and BN layers make it possible to construct nanoscale devices.…”
Section: Introductionmentioning
confidence: 99%